Gli italiani regionali. Atteggiamenti linguistici verso le varietà geografiche dell’italiano - De Pascale, Stefano; Marzo, Stefania (Incontri. Rivista europea di studi italiani, 2016)
Regional Italians: language attitudes toward the geographical varieties of ItalianThis paper explores the opportunities of presented by a direct attitude experiment on regional varieties of the Italian language. It starts with an overview of existing literature on language attitudes, with a special focus on the role of attitudes in standard language change in Italy. Recently, scholars have argued that standardization dynamics can only be understood if one investigates the language attitudes toward the standard language and its varieties. We review the Italian literature on the several new regional varieties of contemporary Italian that are currently involved in the restandardization of the national language, i.e. Milanese, Florentine, Roman and Neapolitan Italian. After this theoretical overview, we report the results of an exploratory, direct attitude experiment (Free Response Task) on these regional varieties. The results show that Milanese Italian triggers (negative) conceptualizations related to high status, while Florentine Italian is positively associated with cultural and historical stereotypes. Roman Italian triggers concepts of vulgarity and Neapolitan Italian receives mixed associations, ranging from cordiality to criminality. The results give rise to the hypothesis that Milanese Italian, and not Roman Italian as its closest competitor, can be considered a good candidate to become the new standard.